2012
DOI: 10.1111/jcpe.12030
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of modified minimally invasive surgical technique in the treatment of human intrabony defects with or without use of rhPDGF‐BB gel – a randomized controlled trial

Abstract: The improvement in both groups could be attributed to the novel surgical technique rather than addition of rhPDGF-BB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 35 publications
3
66
0
1
Order By: Relevance
“…Of the selected studies, 10 were randomized clinical trials (Aimetti, Ferrarotti, Mariani, & Romano, , Cortellini, , Ghezzi, Ferrantino, Bernardini, Lencioni, & Masiero, , Mishra, Avula, Pathakota, & Avula, , Ribeiro, Casarin, Palma, et al, 2011a, Ribeiro et al, , Ribeiro, Casarin, Palma, et al, 2011b, Schincaglia et al, , Trombelli, Simonelli, Pramstraller, Wikesjö, & Farina, , Trombelli, Simonelli, Schincaglia, Cucchi, & Farina, ). All of them had a parallel design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the selected studies, 10 were randomized clinical trials (Aimetti, Ferrarotti, Mariani, & Romano, , Cortellini, , Ghezzi, Ferrantino, Bernardini, Lencioni, & Masiero, , Mishra, Avula, Pathakota, & Avula, , Ribeiro, Casarin, Palma, et al, 2011a, Ribeiro et al, , Ribeiro, Casarin, Palma, et al, 2011b, Schincaglia et al, , Trombelli, Simonelli, Pramstraller, Wikesjö, & Farina, , Trombelli, Simonelli, Schincaglia, Cucchi, & Farina, ). All of them had a parallel design.…”
Section: Resultsmentioning
confidence: 99%
“…Between RCTs, two studies (Trombelli et al, , Schincaglia et al ) compared a single‐flap approach (SFA) with a double‐flap approach (DFA), three studies (Aimetti et al, ; Ribeiro, Casarin, Palma, et al, 2011b; Ribeiro et al, ) compared a minimally invasive surgical technique with a minimally invasive non‐surgical technique or flapless approach and the other five compared the use of different grafts or biologic agents with the same flap design (Cortellini & Tonetti, ; Ghezzi et al, ; Mishra et al, ; Ribeiro, Casarin, Palma, et al, 2011a; Trombelli et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…This approach is supported by three cohort studies [36,37,39] and two controlled studies [40,41]. This approach is supported by a cohort study [38] and three controlled studies [42][43][44]. This approach is supported by a cohort study [38] and three controlled studies [42][43][44].…”
Section: Clinical Studies and Outcomesmentioning
confidence: 88%
“…Furthermore the blood supply of the interdental area seems to be better preserved [68]. Despite the use of regenerative materials, the great importance of surgical flap management and of blood clot stabilization on tissue regeneration was demonstrated in clinical trials that reported improvements in clinical and radiographic outcomes when minimally invasive surgical approaches were used alone or combined with regenerative biomaterials including: hydroxyapatite + membrane, EMD, and PDGF [9, 69, 70]. These microinvasive approaches are indicated when the aesthetic appearance of the area is acceptable and there is no need for coronally advanced flap.…”
Section: Surgical Techniques Evolutionmentioning
confidence: 99%